Sex discrepancy in the reduction of mucosal‐associated invariant T cells caused by obesity - Jianyun Liu; Hongmei Nan; Randy R Brutkiewicz; Jose Casasnovas; Kok Lim Kua (Immunity, Inflammation and Disease)
Abstract Introduction Gut microbiota has been reported to contribute to obesity and the pathology of obesity‐related diseases but the underlying mechanisms are largely unknown. Mucosal‐associated invariant T (MAIT) cells are a unique subpopulation of T cells characterized by the expression of a semi‐invariant T cell receptor (TCR) α chain (Vα19 in mice; Vα7.2 in humans). The expansion and maturation of MAIT cells require the gut microbiota and antigen‐presenting molecule MR1, suggesting that MAIT cells may play a unique role in bridging gut microbiota, obesity, and obesity‐associated inflammation. Methods The levels of human MAIT cells from obese patients, as well as mouse MAIT cells from obese mouse models, were determined by flow cytometry. By comparing to controls, we analyzed the change of MAIT cells in obese subjects. Results We found obese patients had fewer circulating MAIT cells than healthy‐weight donors and the difference was more distinct in male patients. Consistently, male mice (but not female mice) have shown reduced MAIT cells in the liver and adipose tissue after a 10‐week Western diet compared to mice on a control diet. We also explored the possibility of utilizing high‐throughput technology (i.e., quantitative polymerase chain reaction [qPCR]), other than flow cytometry, to determine the expression levels of the invariant TCR of human MAIT cells. But a minimal correlation (R2 = 0.23, p = .11) was observed between qPCR and flow cytometry data. Conclusion Our study suggests that there is a sex discrepancy in the impact of obesity on MAIT cells: MAIT cells in male (but not female) humans and male mice are reduced by obesity.